Microfungal composition in an Astellia-Donatia cushion peatland in Tierra del Fuego, Argentina - Paredes, Noelia Ivana (2014)
Southern Hemisphere peatlands store substantial amounts of soil carbon. Despite their importance in the global carbon cycle, little is known about decomposition processes and the associated fungal diversity. The present study describes the composition of fungal assemblage in two depths from a cushion peatland of predominating Astelia (Asteliaceae) and Donatia (Donatiaceae) species in Moat, Tierra del Fuego. From 48 samples processed, we obtained 338 isolates. Using different culturing methodologies, through direct and microscopic observation and using molecular methods we identified 38 fungal species and 18 genera of Ascomycetes and Zygomycetes. Isolates belonging to Ascomycetes were the most abundant, with dominance of Penicillium and Trichoderma. We described fungal composition and compared species diversity and evenness across two dephts. No differences in the diversity index and evenness were found between depths. The studied peat is an ecosystem that has a great diversity of filamentous fungal species, some of which are described in other peatlands worldwide.